Actuator fault-tolerant control study of an underwater robot with four rotatable thrusters. (1st February 2020) - Kadiyam, Jagadeesh; Parashar, Anjali; Mohan, Santhakumar; Deshmukh, Devendra
Abstract: This paper presents the mathematical design and implementation of an actuator fault-tolerant control system for an underwater robot having four rotatable thrusters where the rotatable action of the thrusters is unconventional to a conventional underwater robotic system. Initially, the dynamic model of the robot is presented. Later, a motion control scheme using a backstepping control technique is made to track a desired spatial trajectory. Two techniques of active fault tolerance control viz., Elimination of Column Method, and Weighted-Pseudo Inverse Method are implemented successfully for single actuator faults on an infinity-shaped trajectory, which is a critical aspect of this study as most of the previous literature reported only on set point control. The methods mentioned above are extended to multiple thrusters failure, but both of them could not handle more than a single thruster failure. Hence, an attempt is made to accommodate two thrusters' failure through the line of sight approach by considering the vehicle as under-actuated. The desired vehicle performance is achieved with this approach. Finally, oceanic currents are modeled to simulate the effectiveness of the methods discussed in the paper to prove the performance capabilities of the control system and fault accommodation schemes under realistic conditions. Highlights: The present robot is a nonlinear system and has the redundancy as that of eight thruster vehicle. The backstepping control scheme is implemented, and the system's stability is ensured by the Lyapunov's method. Two FTC methodologies were implemented to accommodate single thruster faults/failures. Two thrusters' failures were simulated through the line of sight approach by considering the vehicle as under-actuated. Oceanic currents are modeled to prove the performance capabilities of the system under realistic conditions.